2021
DOI: 10.3390/microorganisms9071508
|View full text |Cite
|
Sign up to set email alerts
|

Virological Surveillance and Molecular Characterization of Human Parainfluenzavirus Infection in Children with Acute Respiratory Illness: Germany, 2015–2019

Abstract: Human parainfluenza viruses (HPIVs) are important causes of respiratory illness, especially in young children. However, surveillance for HPIV is rarely performed continuously, and national-level epidemiologic and genetic data are scarce. Within the German sentinel system, to monitor acute respiratory infections (ARI), 4463 respiratory specimens collected from outpatients < 5 years of age between October 2015 and September 2019 were retrospectively screened for HPIV 1–4 using real-time PCR. HPIV was identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 80 publications
(183 reference statements)
3
8
0
Order By: Relevance
“…The results of present study revealed there are significant differences between the age groups and the percentage of HPIV2 positive patients with highest value was (2.00%) of (Less Than 7 Years) . the lowest one was (0%) at age group of (15)(16)(17)(18)(19)(20)(21). While in another study ; Depending on the age group, the prevalence of HPIV types showed significant differences.…”
Section: Discussionmentioning
confidence: 78%
“…The results of present study revealed there are significant differences between the age groups and the percentage of HPIV2 positive patients with highest value was (2.00%) of (Less Than 7 Years) . the lowest one was (0%) at age group of (15)(16)(17)(18)(19)(20)(21). While in another study ; Depending on the age group, the prevalence of HPIV types showed significant differences.…”
Section: Discussionmentioning
confidence: 78%
“…The three examples of respiroviruses with well-studied within-species genetic diversity are HPIV-1, HPIV-3 and BPIV-3. In HPIV-1, three clades (1, 2 and 3) were proposed based on the HN gene [ 10 ]. The mean within-clade p -distance was determined to be 0.0022 to 0.0109, and the between-clade p -distance was between 0.0192 and 0.0368 [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In HPIV-1, three clades (1, 2 and 3) were proposed based on the HN gene [ 10 ]. The mean within-clade p -distance was determined to be 0.0022 to 0.0109, and the between-clade p -distance was between 0.0192 and 0.0368 [ 10 ]. In HPIV-3, six clusters (A, B, C1, C2, C3 and C5) were defined, with the mean within-cluster p -distance ranging from 0.0066 to 0.0325, and a between-cluster p -distance between 0.0262 and 0.0665 [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five hPIV 3-positive samples were randomly selected each year from 2016 and 2021 for ampli cation using the primers HPIV3-Seq_6714_s (5 -AAAGTTACGCAATCCAACTC-3 ), HPIV3_Seq_7400_as (5 -GAGGTATAAGCATAAATCAGA-3 ), HPIV3_Seq_7257_s (5 -CACGTCTGGTCTTCCATCT-3 ), HPIV3_Seq_7929_as (5 -AACAATGATGGAGTTGACCAT-3 ), HPIV3_Seq_7785_s (5 -TGGGTATGGAGGTCTTGAAC-3 ), and HPIV2_Seq_8577_as (5 -TGTCTATTGTCTGATTGCTGATTA-3 ) to generate a 1719-base pair fragment containing the full region of the hemagglutinin-neuraminidase (HN) gene [9]. The amplicons were puri ed using a QIA PCR puri cation kit (Qiagen, Hilden, Germany) and sequenced using appropriate primers [10] in both directions on an ABI-3100 Prism Genetic Analyzer using the BigDye Terminator version 3.1 sequencing kit (Applied Biosystems).…”
Section: Sequencing and Analysismentioning
confidence: 99%